Efficacy of Compounds Isolated from Streptomyces olivaceus against the Morphogenesis and Virulence of Candida albicans - Lili Meng; Changli Sun; Chunyan Zhang; Shihao Song; Xiuyun Sun; Jianhua Ju; Yinyue Deng (Marine Drugs, 2019)
Candida albicans is a type of commensal fungi which causes serious infections in immunocompromised patients and contributes to high mortality. In the present study, we identified that the extract from Streptomyces olivaceus SCSIO T05 inhibited hypha and biofilm formation of C. albicans. Seven compounds were isolated and evaluated for their effects on the biological functions and virulence of C. albicans. Two leading compounds, compound 1 (sorbicillin) and compound 2 (3-methyl-N-(2′-phenethyl)-butyrylamide) were identified as exhibiting strong activity against C. albicans morphological transition, adhesion activity, cytotoxicity, and adhesion to human cells, in a dose-dependent manner. Notably, compound 2 inhibited C. albicans infection in mouse oral mucosal models. Transcriptomic analysis and real-time PCR results revealed that compound 2 most likely inhibited the biological functions of C. albicans cells by regulating the expression levels of HWP1, TEC1, ALS1, IFD6, and CSH1, which are associated with filament formation and cell adhesion. Our results suggest that the candidate compounds present excellent efficacy against C. albicans pathogenicity and that they can be developed as potential options for the clinical treatment of candidiasis.